Dielectric dispersion characteristics of sand contaminated by heavy metal, landfill leachate and BTEX (02-104B) - Lee, JH; Oh, MH; Park, J; Lee, SH; Ahn, KH (ELSEVIER, 2003)
Experiments have been performed to investigate the dielectric properties of contaminated sand. The separate real and imaginary parts of a dielectric constant were investigated in the frequency range of 75 kHz to 12 MHz. The contaminated soils exhibit different complex dielectric dispersion from the uncontaminated soils. The variation in the real dielectric constant can be explained by a polarization mechanism while that in the imaginary dielectric constant by ionic conductivity loss mechanism. The differences of the dielectric behavior with contaminant types suggest that the monitoring of complex dielectric constant has the potential to classify contaminants. The additional analysis for the imaginary part of the dielectric constant can be recommended to obtain the clear information about the state of ionic contaminants in subsurface. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: SOIL-WATER CONTENT; ELECTRICAL-PROPERTIES; CAPACITANCE; CONSTANT